2016
DOI: 10.1038/srep25550
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage Site Localization Differentially Controls Interleukin-6 Receptor Proteolysis by ADAM10 and ADAM17

Abstract: Limited proteolysis of the Interleukin-6 Receptor (IL-6R) leads to the release of the IL-6R ectodomain. Binding of the cytokine IL-6 to the soluble IL-6R (sIL-6R) results in an agonistic IL-6/sIL-6R complex, which activates cells via gp130 irrespective of whether the cells express the IL-6R itself. This signaling pathway has been termed trans-signaling and is thought to mainly account for the pro-inflammatory properties of IL-6. A Disintegrin And Metalloprotease 10 (ADAM10) and ADAM17 are the major proteases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 46 publications
6
77
0
Order By: Relevance
“…Indeed, recombinant ADAM17 cleaved an IL-6R peptide comprising a part of the stalk region, situated two residues N-terminal of QD between Pro355 and Val35648. This cleavage site was further substantiated by molecular modelling49. Interestingly, meprin α and meprin β were found to exhibit a striking preference for negatively charged amino acids at the P1’ position50, which correlates with the previously observed cleavage site in the IL-6R46.…”
supporting
confidence: 75%
“…Indeed, recombinant ADAM17 cleaved an IL-6R peptide comprising a part of the stalk region, situated two residues N-terminal of QD between Pro355 and Val35648. This cleavage site was further substantiated by molecular modelling49. Interestingly, meprin α and meprin β were found to exhibit a striking preference for negatively charged amino acids at the P1’ position50, which correlates with the previously observed cleavage site in the IL-6R46.…”
supporting
confidence: 75%
“…Culture conditions were under a humidified atmosphere (5% of CO 2 ) at 37°C. Generation of HEK293_ADAM10/17 −/− cells was previously described 30 . For transient transfection, cells were seeded in 10 cm cell culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…This SNP encodes amino acid 358 (Asp > Ala) of IL-6R, which is located in the extracellular stalk region and coincides precisely with the cleavage site used by ADAM17 to shed mIL-6R. 62,63 Ferreira et al 55 noted that rs2228145:C was associated with substantially lower (~25% decrease per allele) mIL-6R protein expression in primary immune cell types, despite no significant association with RNA levels of the full-length IL6R transcript (based on n = 88). This suggested that rs2228145:C (358Ala) strongly promotes ADAM17-dependent shedding of mIL-6R.…”
Section: Introductionmentioning
confidence: 94%
“…Second, and perhaps more importantly, rs2228145 is thought to affect mIL‐6R shedding. This SNP encodes amino acid 358 (Asp > Ala) of IL‐6R, which is located in the extracellular stalk region and coincides precisely with the cleavage site used by ADAM17 to shed mIL‐6R . Ferreira et al .…”
Section: Introductionmentioning
confidence: 96%